Antibacterial effects of coniferyl alcohol-derived dehydrogenation polymer on chlamydial infection in vitro - Pfundner, Anna; Weinmayer, Tamara; Geissler, Nora; Kovacevic, Ana; Spasojevic, Dragica; Radotic, Ksenija; Stojanovic, Marijana; Schabussova, Irma; Wiedermann, Ursula; Inic-Kanada, Aleksandra (Frontiers in Chemistry, 2025)
BackgroundChlamydia trachomatis, Gram-negative obligate intracellular bacteria, are a leading cause of sexually transmitted diseases worldwide, often causing severe complications. With no vaccine available and concerns about potential antibiotic resistance, the need for novel treatments is urgent. Dehydrogenation polymer of coniferyl alcohol in alginate hydrogel (DHP/Alg) has not yet been tested against chlamydial infections.Material and MethodsThe cytotoxicity of DHP/Alg on A2EN genital epithelial cells was assessed by measuring cell viability. To investigate its effects on Chlamydia-infected cells, we employed flow cytometry-based assays, fluorescence microscopy, and quantitative PCR (qPCR). Additionally, adhesion assays were performed to examine whether DHP/Alg interferes with Chlamydia entry into host cells.ResultsNo cytotoxic effects of DHP/Alg in tested concentrations on A2EN cells were observed, confirming its safety. Infection and adhesion assays demonstrated a significant reduction in infection levels, suggesting that DHP/Alg directly targets Chlamydia elementary bodies, thereby disrupting their ability to adhere and initiate infection. Fluorescence microscopy revealed that 75 μg/mL DHP/Alg is the most effective dose evaluated to reduce chlamydial infection in vitro, as indicated by the decreased number of inclusions. These findings were further confirmed by qPCR analysis.ConclusionOur results suggest that DHP/Alg is a promising therapeutic option against chlamydial infections. The significant reduction in adhesion levels indicates that DHP/Alg effectively interferes with the initial stages of infection.